Performance Optimization of Bhabinkamtibmas Through the Door-to-Door System in Order to Prevent Criminal Acts of Vehicle Theft in the Law Region of Sragen Resort Police - Papare, Chaleb Chrystal Dwi Putra (Advances in Police Science Research Journal, 2024)
Performance optimalization of Bhanbinkamtibmas (Bhayangkara Pembina Keamanan dan Ketertiban Masyarakat) through Door to Door System can prevent Criminal Act of Vehicle Theft at the law region of Sragen Resort Police. The problem is how to optimize Bhabinkamtibmas performance through Door to Door System activity so that it can prevent Criminal Act of Vehicle Theft at the law region of Sragen Resort Police? This title was employed since nowadays Criminal Act of Vehicle Theft at Sragen Regency is still frequently happened, as well as there are still many weaknesses of Bhabinkamtibmas of Sragen Resort Police. Thisresearch has purpose to get a real portrait of condition of Bhabinkamtibmas performance, Organization Resource management, as well as the synergy of Indonesian National with stakeholder and people’s potency, since there are still many Criminal Acts of Vehicle Theft at Sragen Regency. Analysis descriptive method used in this research focused on analysis and data collection, literature study, and observation, as well as resource statement. To analyze the data, it used qualitative data analysis technique. Theory used is Management, Synergy and Organization Resource Management; as well as some related concepts. As in strategic efforts to optimize Bhabinkamtibmas performance are through Door to Door System by optimizing planning, organization, actuating, as well as controlling management, furthermore, optimizing Human Resource capacity, budgeting support, method used, as well as the availability of facilities and infrastructures to build synergy optimally among Indonesian National Police and government authorities, education agencies, society, entrepreneur, and media.